Hadamard editing of glutathione and macromolecule‐suppressed GABA. (26th October 2017) - Oeltzschner, Georg; Chan, Kimberly L.; Saleh, Muhammad G.; Mikkelsen, Mark; Puts, Nicolaas A.; Edden, Richard A. E.
Abstract : The primary inhibitory neurotransmitter γ‐aminobutyric acid (GABA) and the major antioxidant glutathione (GSH) are compounds of high importance for the function and integrity of the human brain. In this study, a method for simultaneous J ‐difference spectral‐edited magnetic resonance spectroscopy (MRS) of GSH and GABA with suppression of macromolecular (MM) signals at 3 T is proposed. MM‐suppressed Hadamard encoding and reconstruction of MEGA (Mescher–Garwood)‐edited spectroscopy (HERMES) consists of four sub‐experiments (TE = 80 ms), with 20‐ms editing pulses applied at: (A) 4.56 and 1.9 ppm; (B) 4.56 and 1.5 ppm; (C) 1.9 ppm; and (D) 1.5 ppm. One Hadamard combination (A + B – C – D) yields GSH‐edited spectra, and another (A – B + C – D) yields GABA‐edited spectra, with symmetric suppression of the co‐edited MM signal. MM‐suppressed HERMES, conventional HERMES and separate Mescher–Garwood point‐resolved spectroscopy (MEGA‐PRESS) data were successfully acquired from a (33 mm) 3 voxel in the parietal lobe in 10 healthy subjects. GSH‐ and GABA‐edited MM‐suppressed HERMES spectra were in close agreement with the respective MEGA‐PRESS spectra. Mean GABA (and GSH) estimates were 1.10 ± 0.15 i.u. (0.59 ± 0.12 i.u.) for MM‐suppressed HERMES, and 1.13 ± 0.09 i.u. (0.66 ± 0.09 i.u.) for MEGA‐PRESS. Mean GABA (and GSH) differences between MM‐suppressed HERMES and MEGA‐PRESS were –0.03 ± 0.11 i.u. (–0.07 ± 0.11 i.u.). The mean signal‐to‐noise ratio (SNR) improvement of MM‐suppressed HERMES over MEGA‐PRESS was 1.45 ± 0.25 for GABA and 1.32 ± 0.24 for GSH. These results indicate that symmetric suppression of the MM signal can be accommodated into the Hadamard editing framework. Compared with sequential single‐metabolite MEGA‐PRESS experiments, MM‐suppressed HERMES allows for simultaneous edited measurements of GSH and GABA without MM contamination in only half the scan time, and SNR is maintained. Abstract : Hadamard‐encoded J ‐difference‐edited magnetic resonance spectroscopy for simultaneous detection of glutathione and γ‐aminobutyric acid (GABA) with suppression of macromolecular signals is proposed. Simulations and in vivo measurements at 3 T demonstrate the feasibility of this acquisition scheme, and show good qualitative and quantitative agreement with conventional Mescher–Garwood point‐resolved spectroscopy (MEGA‐PRESS) experiments. With this method, glutathione‐edited and macromolecule‐suppressed GABA‐edited spectra can be acquired in half the scan time compared with sequential MEGA‐PRESS acquisitions, with no significant loss of signal‐to‐noise ratio.